2011
DOI: 10.1177/1368430211426733
|View full text |Cite
|
Sign up to set email alerts
|

Does status affect intergroup perceptions of humanity?

Abstract: Across three studies, we examined whether ingroup status may affect intergroup perceptions of\ud humanity. In Studies 1 and 2, we considered real groups: Northern versus Southern Italians; in Study\ud 3, we manipulated the socioeconomic status of two minimal groups. In all studies, members of higher\ud status groups perceived the ingroup as more human than the outgroup, while members of lower status\ud groups did not assign a privileged human status to the ingroup. Such findings were obtained using\ud differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 52 publications
0
38
0
1
Order By: Relevance
“…For the human/animal dimension, we employed five human (bachelor, citizen, human, humans, young boy) and five animal (animal, animals, cub, fauna, specimen) words: the same used as US in the conditioning procedure (see S1 Appendix). In pilot studies [15], we found that the human and animal concepts do not differ in valence. In accordance with IAT procedures, participants were presented with five blocks of practice trials and two blocks of critical trials.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…For the human/animal dimension, we employed five human (bachelor, citizen, human, humans, young boy) and five animal (animal, animals, cub, fauna, specimen) words: the same used as US in the conditioning procedure (see S1 Appendix). In pilot studies [15], we found that the human and animal concepts do not differ in valence. In accordance with IAT procedures, participants were presented with five blocks of practice trials and two blocks of critical trials.…”
Section: Resultsmentioning
confidence: 96%
“…As CS, we used six typical Moroccan faces (males); as US, we used uniquely human words (humanization condition) or non-uniquely human and animal-related words (dehumanization condition). The uniquely human words were: four uniquely human traits (e.g., rationality, morality; see [4]); six secondary emotions–three positive (e.g., pride, optimism) and three negative (e.g., regret, shame); five words expressing concepts unique to the human species (e.g., humans and citizen [15]). The non-uniquely human or animal-related words were: four non-uniquely human traits (e.g., instinct, impulsiveness [4]); six primary emotions–three positive (e.g., pleasure, excitement) and three negative (e.g., rage, pain); five words expressing concepts unique to the animal category (e.g., animals and cub [15]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research determined that participants have less dehumanization attitude toward correspondents from the same socio-economic status than they have toward those from different statuses (Leyens et al, 2001). Another study revealed that those from higher status groups have dehumanizing attitudes toward those from lower status; however, those from lower status groups do not share this attitude toward those from higher status groups (Capozza et al, 2012). Doctors' socio-economic statuses may cause them to dehumanize patients, especially those from lower socio-economic statuses.…”
Section: High Statusmentioning
confidence: 99%